A case of concomitant EGFR/ALK alteration against a mutated EGFR background in early-stage lung adenocarcinoma - Ki-Chang Lee; Jiwon Koh; Doo Hyun Chung; Yoon Kyung Jeon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Rare cases of lung adenocarcinoma (LUAD) with concomitant epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) translocation have been reported. However, their clonal and evolutional relationship remains unclear. We report a case of early-stage EGFR-mutated LUAD with a focal concomitant EGFR/ALK alteration. A 63-year-old male underwent lobectomy to remove a 1.9-cm-sized lung nodule, which was diagnosed with EGFR-mutated LUAD. ALK immunohistochemistry (IHC) showed focal positivity within the part of the tumor characterized by lepidic pattern, also confirmed by fluorescence in-situ hybridization (FISH). Targeted next-generation sequencing was performed separately on the ALK IHC/FISH-positive and -negative areas. EGFR L833V/L858R mutations were detected in both areas, whereas EML4 (echinoderm microtubule-associated protein-like 4)-ALK translocations was confirmed only in the ALK IHC/FISH-positive area, suggesting the divergence of an EGFR/ALK co-altered subclone from the original EGFR-mutant clone. Our study suggests that concurrent alterations of EGFR and ALK can arise via divergent tumor evolution, even in the relatively early phases of tumorigenesis.